Experimental Study of Composite Members in Spatial Grid Structure Subjected to Ultralow-Cyclic Axial Force - Jie Zhang; Haiwang Li; Xiayun Song (Advances in Civil Engineering)
This paper presents the results of ultralow-cycle fatigue tests for three full-scale assemblies consisting of steel tubes and bolt-sphere joints, which are widely used in public buildings. Each assembly was tested six times under a varying loading history. The ultralow-cycle fatigue performance was investigated considering the joint stiffness and loading history. The deformation patterns, hysteretic characteristics, skeleton curves, bearing-capacity degradation features, cumulative energy dissipation, and cumulative damage index of the assembly were obtained and analysed. The results show that the joint stiffness and loading system have a significant effect on the ultralow-cycle fatigue performance of the assembly. Based on these results, an equation that describes the relationship between the cumulative damage index and the bearing degradation of the assembly for an ultralow-cycle fatigue test was derived.